2021
DOI: 10.1126/sciadv.abj3397
|View full text |Cite
|
Sign up to set email alerts
|

Introgression from farmed escapees affects the full life cycle of wild Atlantic salmon

Abstract: Early and late life history and growth are affected by farmed salmon introgression across 105 wild populations of Atlantic salmon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 71 publications
5
28
0
Order By: Relevance
“…Our results showed that the magnitude of change for most of the admixture‐influenced traits was modest. This observation is consistent with the results of similar previous studies (Bolstad et al, 2017, 2021; Skaala et al, 2019). The results of modeling the effect of admixture on life history traits of wild Atlantic salmon populations following introgression from domesticated and directionally selected conspecifics also indicate that under low to modest intrusion scenarios, the mean population change is likely to be weak and potentially undetectable (Castellani et al, 2015, 2018).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results showed that the magnitude of change for most of the admixture‐influenced traits was modest. This observation is consistent with the results of similar previous studies (Bolstad et al, 2017, 2021; Skaala et al, 2019). The results of modeling the effect of admixture on life history traits of wild Atlantic salmon populations following introgression from domesticated and directionally selected conspecifics also indicate that under low to modest intrusion scenarios, the mean population change is likely to be weak and potentially undetectable (Castellani et al, 2015, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Two earlier studies based on 62 and 105 Atlantic populations, respectively (Bolstad et al, 2017, 2021) indicated a high variability of the effect of admixture on sea age, with results showing that admixture may lead to both increases and decreases in age at maturation of males and females, depending on the genetic background of the recipient wild population. Our observation of a male‐specific decrease in age at maturation in the river Etne raises two points for discussion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Increasing water temperature has been identified as being a principal driver of the phenomenon (Kovach et al, 2013;Arevalo et al, 2020;Teichert et al, 2020) and modeling experiments using future climate projections indicate that earlier runs of fish are increasingly likely (Hedger et al, 2013;Teichert et al, 2020). While it is tempting to attribute any significant changes in migration phenology to the direct effects of climate warming, these species are impacted by interacting multiple stressors, including fishing, land use change, introgression with captive-bred individuals, food web disruption, the presence of dams and the incidence of parasites (Palstra et al, 2007;Belletti et al, 2020;Bolstad et al, 2021;Sobocinski et al, 2021;Tillotson et al, 2021). Shifts in phenology are therefore likely to be context-dependent, but worth exploring as we strive to understand, mitigate and adapt to the interconnected impacts of climate change and biodiversity loss on ecosystems.…”
Section: Introductionmentioning
confidence: 99%